Application of the sufficiency economy philosophy to develop quality of life - aKnit , Thanakit (RATANABUTH JOURNAL, 2020)
The Sufficiency Economy Philosophy has the important role in human development. Sufficiency economy is the philosophy that come from the speech of King Bhumibol. Which has an idea that thai people are modesty, have a reason and the good immunity by the knowledge and virtue. Make people at the center of development, which has concepts that are consistent with human resource economics. That focus in studying investment in people to become the human capital that can produce more products and services. Sufficiency Economy Philosophy also invests in people development to increase social capital. Sufficiency Economy Philosophy is an applied philosophy that can be applied in many social dimensions. It’s not just the image that the media creates, and society understands that it is in the matter of agriculture, growing, raising animals for economical sustenance. But the sufficiency economy philosophy is the main important of improving the quality of life people at all levels. Every different make for sustainable progress, It’s a matter of having a good quality of life. Because self-sufficiency is a thought process that relies on wisdom to be careful in applying various development. Along with a sense of virtue honesty and to have the right knowledge, wisdom, which will result in balance and readiness to be changes that occur all the time in terms of resources, environment, culture, lifestyle and society.